Fostering Critical Thinking Skills and Scientific Epistemological Beliefs through Flipbook-Assisted POE2WE - Pitaloka, Nanda Ayu; Inayah, Nailil; Huda, Muhammad Nuril; Setyawati, Maunah; Indratno, Dwi (Journal of Natural Science and Integration, 2024)
This research aims to improve critical thinking skills and Scientific Epistemological Beliefs (SEB) through Flipbook-Assisted Predict Observe Explain Elaboration Write Evaluation (POE2WE) learning model. Critical thinking and good SEB are educational mandates in the curriculum and 21st-century skills. This research was conducted in two classes, namely classes 7A and 7B at the SIKL. This research was a quantitative experiment using posttest-only nonequivalent group. The instruments used to collect data are critical thinking tests and SEB questionnaires. The results of the critical thinking test were analyzed using the Independent Sample T-test. The t-test results obtained were 0.89, greater than 0.05. The highest indicator of critical thinking ability is Basic Clarification with an average score of 91,37. Meanwhile, students SEB were reviewed from the results of filling out the questionnaire, the highest indicator obtained was source with a response of 56.9%. Thus, using the Flipbook-Assisted POE2WE model can significantly improve students' critical thinking skills and SEB.Keywords: critical thinking skills, science epistemological beliefs (SEB), predict observe explain elaboration write evaluation (POE2WE), flipbook, 21st-century skills